Waterborne polyurethane resin and porphyrin-based lithium-sulfur battery electrode binder prepared from waterborne polyurethane resin
By using polymer aqueous polyurethane resin with carboxyl groups in the molecular chain in lithium sulfur batteries for in situ crosslinking with porphyrin/metaloporphyrin, a lithium sulfur battery electrode water-based binder with electrocatalytic properties was prepared, which solved the problem of capacity decline and poor cycle stability of lithium sulfur batteries during circulation, and achieved higher capacity retention and better rate performance.
Patent Information
- Application Number
- CN202411762737.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
During the circulation process, lithium sulfur batteries have a "shuttle effect" of lithium polysulfide, the volume expansion of the positive electrode and the low conductivity of active substances, resulting in a decline in capacity and poor circulation stability, which affects the service life of the battery.
The polymer aqueous polyurethane resin with carboxyl groups in the molecular chain was used for in-situ crosslinking with porphyrin/metaloporphyrin to prepare a lithium sulfur battery electrode aqueous binder with electrocatalytic properties. The binder inhibits the "shuttle effect" by adsorbing lithium polysulfide and catalyzing its conversion, and withstands the volume change of the positive electrode through excellent mechanical properties.
The initial discharge capacity, capacity retention rate and charge and discharge voltage polarization of lithium-sulfur batteries are improved, which significantly improves the cycle stability and rate performance of the battery and extends the service life of the battery.
Smart Images

Figure CN119798595A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur battery binders, in particular to a waterborne polyurethane resin and a porphyrin-based lithium-sulfur battery electrode binder prepared using the waterborne polyurethane resin, in particular to a polymer waterborne polyurethane resin having carboxyl groups in its molecular chain and a preparation method thereof, and a lithium-sulfur battery electrode waterborne binder with electrocatalytic performance prepared by in-situ crosslinking of the waterborne polyurethane resin with porphyrin / metalloporphyrin. Background Art
[0002] In 1800, Alessandro Volta first proposed the working principle of the battery and demonstrated a device that could generate continuous current. Since then, battery technology has continued to develop and progress. Lead-acid batteries, nickel-metal hydride batteries, nickel-cadmium batteries and other technologies have been continuously developed and are close to the limit of improvement. Lithium battery technology has received widespread attention and rapid development in recent years. Since its commercialization, it has become an irreplaceable product in the field of electrochemical energy storage. Lithium-ion batteries (LIBs) have ultra-long life and high energy density. They are currently widely used in electronic products and electric vehicles. Compared with general primary batteries, they also have the advantages of high operating voltage, wide operating temperature, stable discharge and low self-discharge rate. In recent years, my country's lithium battery industry has also achieved rapid growth, accounting for more than 70% of global production capacity. However, in recent years, due to the rapid development of electric vehicles, energy fields and electronic equipment industries, the energy density of lithium-ion batteries has approached its theoretical limit, and it is difficult to achieve greater breakthroughs. Therefore, lithium batteries with higher specific capacity and higher energy density have become the research direction of more researchers.
[0003] Among the many new lithium batteries, lithium-sulfur batteries are one of the most widely-watched candidates. Lithium-sulfur batteries generally use single-element lithium as the negative electrode, a composite prepared from single-element sulfur, a conductive agent, and a binder as the positive electrode, a porous polymer as a separator, and an electrolyte to conduct lithium ions to complete energy conversion. Due to its high energy density, low cost, environmental friendliness, and wide sources, lithium-sulfur batteries are considered to be one of the options for the next generation of commercial lithium batteries. However, during the cycle of lithium-sulfur batteries, the "shuttle effect" of lithium polysulfide, the volume expansion of the positive electrode, and the low conductivity of the active material will lead to a decline in the capacity of lithium-sulfur batteries, affecting the cycle stability of lithium-sulfur batteries and even causing battery failure.
[0004] Electrode binders play an important role in positive electrode materials. They can inhibit the diffusion of lithium polysulfide to the negative electrode while maintaining the structural stability of the positive electrode. A good electrode binder needs to be able to maintain the contact between the active material and the conductive agent, maintain the stability of the positive electrode structure, and stabilize the electrode material on the current collector. It also needs to be able to disperse in the solvent while maintaining good mechanical strength. Compared with ordinary lithium-ion batteries, the positive electrode material of lithium-sulfur batteries will also undergo phase changes during the charging and discharging process, so the electrode binder needs to have a certain affinity for lithium polysulfide. In addition, due to the volume expansion problem of the positive electrode during the discharge of lithium-sulfur batteries, the binder needs to have excellent mechanical properties to withstand the problem of volume changes.
[0005] The commercial electrode binder polyvinylidene fluoride (PVDF) has good electrochemical stability, but can only play a basic bonding role. The volume change of sulfur after multiple cycles will cause cracks in the electrode structure, leading to electrode failure. At the same time, the binding force between PVDF and lithium polysulfide is very weak, and it is difficult to suppress the "shuttle effect" of lithium polysulfide, resulting in unsatisfactory cycle performance. When using PVDF as a binder, toxic and flammable N-methylpyrrolidone (NMP) is also required as a solvent, which will cause certain damage to the environment. Summary of the invention
[0006] In order to solve the problems raised by the above-mentioned prior art, the present invention provides an aqueous polyurethane resin and a porphyrin-based lithium-sulfur battery electrode binder prepared using the same. The first invention purpose is to provide a polymer aqueous polyurethane resin having a carboxyl group in the molecular chain and a preparation method thereof. The second invention purpose is to prepare an aqueous lithium-sulfur battery electrode aqueous binder with electrocatalytic performance by in-situ crosslinking of the aqueous polyurethane resin and porphyrin / metalloporphyrin. The aqueous lithium-sulfur battery electrode binder has higher initial discharge capacity, higher capacity retention rate and lower charge and discharge voltage polarization than commercial electrode binders, providing a new idea and solution for the development of high-performance lithium-sulfur batteries.
[0007] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.
[0008] In one aspect, the present invention provides a high molecular weight waterborne polyurethane resin having a carboxyl group in its molecular chain, and its chemical structure is as follows:
[0009]
[0010] Wherein, n=1-100, R1 is the following structure:
[0011]
[0012] R2 is any of the following structures:
[0013]
[0014] R3 is any one of the following structures, m=10-200:
[0015]
[0016] In the above chemical structural formula, “…” indicates the position where the chemical bonds are connected.
[0017] On the other hand, the present invention also provides a method for preparing the polymer waterborne polyurethane resin having carboxyl groups in the above molecular chain, which is prepared by condensation polymerization of polymerized diols, 2,2-dimethylol propionic acid, N-methyldiethanolamine and diisocyanate as raw materials to obtain an isocyanate-terminated prepolymer, and then sequentially salt-formed to neutralize the carboxyl groups, emulsify, and chain extend to obtain the polymer waterborne polyurethane resin having carboxyl groups in the molecular chain. It should be noted that those skilled in the art can obtain specific preparation steps based on the raw material selection and reaction sequence shown above, especially can balance the raw materials according to the common knowledge in the art through the above specific chemical structural formula; therefore, the technical scheme provided below by the present invention does not mean the sole designation or limitation of the method for preparing the polymer waterborne polyurethane resin having carboxyl groups in the molecular chain.
[0018] The present invention also provides a method for preparing a high molecular weight waterborne polyurethane resin having carboxyl groups in its molecular chain, comprising the following steps:
[0019] Polymeric diol, 2,2-dihydroxymethylpropionic acid, N-methyldiethanolamine and diisocyanate are selected as raw materials, mixed evenly and reacted at a temperature of 30-100° C. for 0.5-12 hours to prepare an isocyanate-terminated prepolymer; the prepolymer is then cooled to 0-80° C., neutralized with a carboxyl group and subjected to a salt treatment, and then emulsified and chain extended using a water-soluble diamine as a chain extender to prepare a high molecular weight waterborne polyurethane resin having a carboxyl group in the molecular chain.
[0020] Herein, the polymeric diol is a polymer obtained by polymerization of a monomer having two hydroxyl groups, for example, any one of polyethylene glycol, polypropylene glycol and polytetramethylene glycol, and the molecular weight of the polymeric diol is in the range of 600 to 10000. Those skilled in the art can directly select commercially available conventional chemical raw material grade raw materials.
[0021] In one of the technical solutions, the polymeric diol is used as the flexible soft segment of the waterborne polyurethane, preferably polyethylene glycol, with a molecular weight of about 1000.
[0022] In this article, 2,2-dimethylolpropionic acid is an alkyl compound with propionic acid side chains and two hydroxyl groups, which is introduced into the molecular chain through the reaction of hydroxyl groups and isocyanate to provide chemical sites for subsequent cross-linking. Usually, commercially available conventional chemical raw material grade raw materials are directly selected.
[0023] Herein, the diisocyanate is a compound having two isocyanate groups, for example, any one of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, toluene diisocyanate and hexamethylene diisocyanate. Those skilled in the art can directly select commercially available conventional chemical raw material grade raw materials.
[0024] In one technical solution, the diisocyanate is preferably isophorone diisocyanate.
[0025] Herein, the polymeric diol, 2,2-dimethylolpropionic acid, N-methyldiethanolamine and diisocyanate are raw materials, and their specific proportions can be balanced according to the above specific chemical formula according to the ratio of isocyanate, hydroxyl and amino groups according to the molar ratio required for the reaction.
[0026] In order to better illustrate the present invention and provide a technical solution for reference, the molar ratio of the polymer diol, 2,2-dihydroxymethylpropionic acid, N-methyldiethanolamine and diisocyanate is 1: (1-1.5): (1-1.5): (4-8).
[0027] In this article, the neutralization carboxyl salt treatment is to neutralize the prepolymer with carboxyl groups in the molecular chain and isocyanate-terminated to form salts through the reaction of amino and carboxyl groups to enhance hydrophilicity for dispersion and emulsification. Those skilled in the art should know that the specific method of the neutralization carboxyl salt treatment adopted in the present invention is common knowledge in the art, such as adding triethylamine (TEA) to neutralize the carboxyl salt treatment, wherein the molar ratio of carboxyl and triethylamine in the isocyanate-terminated prepolymer is 1: (1 to 1.5), and under laboratory conditions, the molar ratio of 2,2-dimethylol propionic acid and triethylamine can be selected to be 1: (1 to 1.5).
[0028] In this article, the emulsification is to uniformly disperse the prepolymer treated with salt in an immiscible liquid to form a prepolymer emulsion. Those skilled in the art should know that the specific emulsification method used in the present invention is common knowledge in the field, such as adding to deionized water for uniform dispersion and emulsification.
[0029] In order to better illustrate the present invention and provide a technical solution for reference, the emulsification is specifically adding deionized water for uniform dispersion and emulsification, and the amount of deionized water added is 0.5 to 5 times the mass of the prepolymer treated with salt.
[0030] In one of the technical solutions, the water-soluble diamine is selected from any one of ethylenediamine, propylenediamine, butylenediamine, pentamethylenediamine and hexamethylenediamine; and the molar ratio of the chain extender to the diisocyanate is (0.5-1.5):1.
[0031] It should be noted that the specific reaction conditions for chain extension using a water-soluble diamine as a chain extender are based on the selected chain extender and are carried out in accordance with the common knowledge in the art or the relevant instructions for use of the chain extender.
[0032] In order to better illustrate the present invention and provide a technical solution for reference, when the water-soluble diamine is ethylenediamine, ethylenediamine is added dropwise to the emulsified prepolymer emulsion and stirred for reaction at a temperature of 0 to 80° C. for 1 to 10 hours.
[0033] On the other hand, the present invention also provides a lithium-sulfur battery electrode aqueous binder with electrocatalytic performance prepared by in-situ crosslinking of the above-mentioned aqueous polyurethane resin and porphyrin / metalloporphyrin, which mainly comprises the following steps:
[0034] Tetrakis(4-carboxyphenyl)porphyrin / tetrakis(4-carboxyphenyl)porphyrin metal complex and waterborne polyurethane resin are added into a reaction container in a mass ratio of 1:(1-20), a crosslinking agent is added, and the mixture is fully stirred to obtain a waterborne binder for lithium-sulfur battery electrodes with electrocatalytic properties.
[0035] In this article, the tetrakis(4-carboxyphenyl)porphyrin (CAS: 14609-54-2) is a conventional commercially available chemical raw material and an important porphyrin compound, which can form porphyrin metal complexes with a variety of metal ions. In the present invention, when the tetrakis(4-carboxyphenyl)porphyrin metal complex is selected, compared with tetrakis(4-carboxyphenyl)porphyrin, the porphyrin metal complex has the advantages of strong adsorption of lithium polysulfide and catalytic conversion of lithium polysulfide.
[0036] In one of the technical solutions, the tetrakis(4-carboxyphenyl)porphyrin metal complex is a metal complex formed by tetrakis(4-carboxyphenyl)porphyrin and any one of iron ions, cobalt ions, nickel ions, and manganese ions; the tetrakis(4-carboxyphenyl)porphyrin metal complex is prepared by mixing tetrakis(4-carboxyphenyl)porphyrin with a metal salt and conducting a metalation reaction.
[0037] In order to better illustrate the present invention and provide a technical solution for reference, the preparation method of the tetrakis(4-carboxyphenyl)porphyrin metal complex is specifically to dissolve the tetrakis(4-carboxyphenyl)porphyrin in an organic solvent, add a metal salt, heat to 50-180°C and reflux for 1-12 hours, and then sequentially precipitate, filter, wash and dry to obtain the tetrakis(4-carboxyphenyl)porphyrin metal complex; wherein the metal salt is selected to include any one of ferric chloride, cobalt chloride, nickel chloride and magnesium chloride, and the molar ratio of the tetrakis(4-carboxyphenyl)porphyrin to the metal salt is 1:(1-1.5).
[0038] In the above technical scheme, the cross-linking agent is a cross-linking agent commonly used in the technical field for in-situ cross-linking reactions. Technicians in the technical field can select a suitable cross-linking agent according to actual needs, for example, trimethylolpropane-tris[3-(2-methylaziridinyl)acrylate] is preferred, and the molar ratio of the aziridinyl group in the cross-linking agent to the carboxyl group in the waterborne polyurethane resin and the tetrakis(4-carboxyphenyl)porphyrin / tetrakis(4-carboxyphenyl)porphyrin metal complex is 1:(0.8~1.5).
[0039] Herein, the stirring is a stirring operation conventionally used in the art, including magnetic stirring or mechanical stirring, and those skilled in the art can select a suitable stirring method according to the production scale or the current process conditions. In one technical solution, the stirring can be performed at a stirring rate of 100 to 800 rpm.
[0040] On the other hand, based on the aqueous binder for lithium-sulfur battery electrodes having electrocatalytic properties prepared as described above, in order to better illustrate the present invention and provide a reference application mode, the present invention also provides a method for preparing a sulfur electrode based on the aqueous binder for lithium-sulfur battery electrodes having electrocatalytic properties, comprising the following steps:
[0041] (1) Prepare the following raw materials by weight:
[0042] 50-90 parts of carbon-sulfur compound,
[0043] 3-20 parts of conductive carbon for electrodes,
[0044] 5 to 30 parts of aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties;
[0045] (2) The carbon-sulfur composite, the conductive carbon for the electrode, and the aqueous binder for the lithium-sulfur battery electrode having electrocatalytic performance prepared in step (1) are fully mixed and then coated on the surface of the electrode current collector by scraping, and dried to obtain a sulfur electrode.
[0046] In step (1), the carbon-sulfur composite is selected from conventional components in the sulfur electrode of a lithium-sulfur battery in the technical field. Those skilled in the art can know how to select and obtain the carbon-sulfur composite based on the records of lithium-sulfur batteries in the prior art.
[0047] In order to better illustrate the present invention and provide a technical solution for reference, the specific preparation method of the carbon-sulfur composite in step (1) is to mix the sublimated sulfur and carbon nanotubes in a weight ratio of 7:3 by ball milling, transfer the mixture to a reaction container, and heat the mixture at 155-160° C. for 15-20 hours under inert gas protection to obtain the carbon-sulfur composite.
[0048] In step (1), the conductive carbon for electrode is selected from conventional components in the sulfur electrode of lithium-sulfur batteries in the technical field. Those skilled in the art can know how to select and obtain conductive carbon for electrode based on the records of lithium-sulfur batteries in the prior art.
[0049] In order to better illustrate the present invention and provide a technical solution for reference, the conductive carbon for the electrode in step (1) is selected to include at least one of conductive carbon black, graphene, and carbon nanotubes.
[0050] In step (2), the fully mixing follows the principle of conventional chemical common sense, and the components are mixed evenly by means of mechanical stirring, etc. Under laboratory conditions, mechanical mixing for 10 to 30 minutes is usually sufficient to achieve a fully mixed effect. Considering the industrial scale-up effect, in the actual implementation of the conversion process, those skilled in the art may adopt a more appropriate fully mixing procedure according to the blending conditions of the components.
[0051] In this article, the scraping method in step (2) follows the common chemical common sense principle, and those skilled in the art can directly refer to the conventional dry electrode technology or the conventional film-forming method suitable for preparing sulfur electrodes reported in the literature.
[0052] In step (2), the electrode current collector is selected from conventional components in the sulfur electrode of a lithium-sulfur battery in the technical field. Those skilled in the art can know how to select and obtain the electrode current collector based on the records of lithium-sulfur batteries in the prior art.
[0053] It should be noted that if the coating does not have a suitable viscosity before the step (2), a small amount of solvent may be added.
[0054] The present invention has the following beneficial effects:
[0055] 1. The aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties provided by the present invention has been tested to have a large number of nitrogen-containing polar groups (pyrrole nitrogen, carbamate group, urea group and amine group, etc.) and metal ions that can adsorb lithium polysulfide when used as a binder, and can inhibit the shuttling of lithium polysulfide by adsorption.
[0056] 2. The aqueous binder for lithium-sulfur battery electrodes with electrocatalytic performance provided by the present invention has been tested to be able to maintain a discharge capacity of 724 mAh g after 200 cycles at 1C when used as a binder. -1 , showing good cycle stability.
[0057] 3. The aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties provided by the present invention has been tested to be a binder. Compared with the conventional commercial battery binder used in the prior art, the prepared sulfur electrode has better rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a schematic diagram of the chemical structure of the aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties prepared in Example 3 of the present invention.
[0059] Figure 2 The stripping force-displacement result comparison diagram of the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1 and the result photos after the stripping experiment. Among them, Figure (a) is a stripping force-displacement result comparison diagram of the sulfur electrode samples prepared in Example 7 and Comparative Example 1 in the sulfur positive electrode stripping experiment; Figure (b) is a result photo of the sulfur electrode samples prepared in Example 7 and Comparative Example 1 after the sulfur positive electrode stripping experiment.
[0060] Figure 3 The swelling ratio comparison bar graph and the photos after immersion of the sulfur electrode samples prepared in Example 7 and Comparative Example 1 of the present invention are shown in Figure (a) and Figure (b) are photos of the sulfur electrode samples prepared in Example 7 and Comparative Example 1 after being immersed in 1 mL of LS-001 electrolyte for 12 hours.
[0061] Figure 4 This is a comparative curve of the long cycle performance of batteries assembled from the sulfur electrode samples prepared in Examples 6 to 9 of the present invention and Comparative Example 1 after 200 cycles at 1C.
[0062] Figure 5 It is a comparison chart of rate performance curves of batteries assembled from the sulfur electrode samples prepared in Examples 6 to 9 of the present invention and Comparative Example 1.
[0063] Figure 6GITT curves at 0.1C of batteries assembled from the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1.
[0064] Figure 7 This is a comparison graph of EIS of batteries assembled from the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1.
[0065] Figure 8 The cyclic voltammetry comparison curves of the batteries assembled with the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1 are shown.
[0066] Fig. 9 The sulfur electrode and diaphragm morphology photos of the battery assembled with the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1 after 200 cycles at 1C. Among them, Figure (a) is a photo of the sulfur electrode morphology of the battery assembled with the sulfur electrode sample prepared in Example 7 after 200 cycles at 1C; Figure (b) is a photo of the sulfur electrode morphology of the battery assembled with the sulfur electrode sample prepared in Comparative Example 1 after 200 cycles at 1C; Figure (c) is a photo of the diaphragm morphology of the battery assembled with the sulfur electrode sample prepared in Example 7 after 200 cycles at 1C; Figure (d) is a photo of the diaphragm morphology of the battery assembled with the sulfur electrode sample prepared in Comparative Example 1 after 200 cycles at 1C. DETAILED DESCRIPTION
[0067] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.
[0068] In one aspect, the present invention provides a high molecular weight waterborne polyurethane resin having a carboxyl group in its molecular chain, and its chemical structure is as follows:
[0069]
[0070] Wherein, n=1-100, R1 is the following structure:
[0071]
[0072] R2 is any of the following structures:
[0073]
[0074] R3 is any one of the following structures, m=10-200:
[0075]
[0076] In the above chemical structural formula, “…” indicates the position where the chemical bonds are connected.
[0077] On the other hand, the present invention also provides a method for preparing the polymer waterborne polyurethane resin having carboxyl groups in the above molecular chain, which is prepared by condensation polymerization of polymerized diols, 2,2-dimethylol propionic acid, N-methyldiethanolamine and diisocyanate as raw materials to obtain an isocyanate-terminated prepolymer, and then sequentially salt-formed to neutralize the carboxyl groups, emulsify, and chain extend to obtain the polymer waterborne polyurethane resin having carboxyl groups in the molecular chain. It should be noted that those skilled in the art can obtain specific preparation steps based on the raw material selection and reaction sequence shown above, especially can balance the raw materials according to the common knowledge in the art through the above specific chemical structural formula; therefore, the technical scheme provided below by the present invention does not mean the sole designation or limitation of the method for preparing the polymer waterborne polyurethane resin having carboxyl groups in the molecular chain.
[0078] The present invention also provides a method for preparing a high molecular weight waterborne polyurethane resin having carboxyl groups in its molecular chain, comprising the following steps:
[0079] Polymeric diol, 2,2-dihydroxymethylpropionic acid, N-methyldiethanolamine and diisocyanate are selected as raw materials, mixed evenly and reacted at a temperature of 30-100° C. for 0.5-12 hours to prepare an isocyanate-terminated prepolymer; the prepolymer is then cooled to 0-80° C., neutralized with a carboxyl group and subjected to a salt treatment, and then emulsified and chain extended using a water-soluble diamine as a chain extender to prepare a high molecular weight waterborne polyurethane resin having a carboxyl group in the molecular chain.
[0080] Herein, the polymeric diol is a polymer obtained by polymerization of a monomer having two hydroxyl groups, and in one embodiment, for example, includes any one of polyethylene glycol, polypropylene glycol and polytetramethylene glycol, and the molecular weight of the polymeric diol ranges from 600 to 10000. Those skilled in the art can directly select commercially available conventional chemical raw material grade raw materials.
[0081] In one embodiment, the polymeric diol is used as the flexible soft segment of the waterborne polyurethane, preferably polyethylene glycol, with a molecular weight of about 1000.
[0082] In this article, 2,2-dimethylolpropionic acid is an alkyl compound with propionic acid side chains and two hydroxyl groups, which is introduced into the molecular chain through the reaction of hydroxyl groups and isocyanate to provide chemical sites for subsequent cross-linking. Usually, commercially available conventional chemical raw material grade raw materials are directly selected.
[0083] In this article, the diisocyanate is a compound having two isocyanate groups, and in one embodiment, for example, includes any one of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, toluene diisocyanate and hexamethylene diisocyanate. Those skilled in the art can directly select commercially available conventional chemical raw material grade raw materials.
[0084] In one embodiment, the diisocyanate is preferably isophorone diisocyanate.
[0085] Herein, the polymeric diol, 2,2-dimethylolpropionic acid, N-methyldiethanolamine and diisocyanate are raw materials, and their specific proportions can be balanced according to the above specific chemical formula according to the ratio of isocyanate, hydroxyl and amino groups according to the molar ratio required for the reaction.
[0086] In order to better illustrate the present invention and provide an implementation method for reference, the molar ratio of the polymer diol, 2,2-dihydroxymethylpropionic acid, N-methyldiethanolamine and diisocyanate is 1: (1-1.5): (1-1.5): (4-8).
[0087] In this article, the neutralization carboxyl salt treatment is to neutralize the prepolymer with carboxyl groups in the molecular chain and isocyanate-terminated to form salts through the reaction of amino and carboxyl groups to enhance hydrophilicity and facilitate dispersion and emulsification. Those skilled in the art should know that the specific method of the neutralization carboxyl salt treatment adopted in the present invention is common knowledge in the art. In one embodiment, for example, triethylamine (TEA) is added to neutralize the carboxyl salt treatment, wherein the molar ratio of carboxyl and triethylamine in the isocyanate-terminated prepolymer is 1: (1 to 1.5). Under laboratory conditions, the molar ratio of 2,2-dimethylol propionic acid and triethylamine can be selected to be 1: (1 to 1.5), such as 1: 1, 1: 1.1, 1: 1.2, 1: 1.3, 1: 1.4, 1: 1.5 or any range or point value therebetween.
[0088] In this article, the emulsification is to uniformly disperse the prepolymer treated with salt in an immiscible liquid to form a prepolymer emulsion. Those skilled in the art should know that the specific emulsification method used in the present invention is common knowledge in the field, such as adding to deionized water for uniform dispersion and emulsification.
[0089] In order to better illustrate the present invention and provide an implementation method for reference, the emulsification is specifically to add deionized water for uniform dispersion and emulsification, and the amount of deionized water added is 0.5 to 5 times the mass of the prepolymer after salt treatment, for example, 0.5 times, 0.6 times, 0.8 times, 1 times, 1.5 times, 2 times, 2.5 times, 3 times, 3.5 times, 4 times, 4.5 times, 5 times or any range or point value therebetween.
[0090] In one embodiment, the water-soluble diamine is selected from any one of ethylenediamine, propylenediamine, butylenediamine, pentanediamine and hexamethylenediamine; the molar ratio of the chain extender to the diisocyanate is (0.5-1.5):1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1 times or any range or point value therebetween.
[0091] It should be noted that the specific reaction conditions for chain extension using a water-soluble diamine as a chain extender are based on the selected chain extender and are carried out in accordance with the common knowledge in the art or the relevant instructions for use of the chain extender.
[0092] In order to better illustrate the present invention and provide an implementation method for reference, when the water-soluble diamine is ethylenediamine, ethylenediamine is added dropwise to the emulsified prepolymer emulsion and stirred at a temperature of 0 to 80° C. for 1 to 10 hours.
[0093] On the other hand, the present invention also provides a lithium-sulfur battery electrode aqueous binder with electrocatalytic performance prepared by in-situ crosslinking of the above-mentioned aqueous polyurethane resin and porphyrin / metalloporphyrin, which mainly comprises the following steps:
[0094] Tetrakis(4-carboxyphenyl)porphyrin / tetrakis(4-carboxyphenyl)porphyrin metal complex and waterborne polyurethane resin are added into a reaction container in a mass ratio of 1:(1-20), a crosslinking agent is added, and the mixture is fully stirred to obtain a waterborne binder for lithium-sulfur battery electrodes with electrocatalytic properties.
[0095] In this article, the tetrakis(4-carboxyphenyl)porphyrin (CAS: 14609-54-2) is a conventional commercially available chemical raw material and an important porphyrin compound, which can form porphyrin metal complexes with a variety of metal ions. In the present invention, when the tetrakis(4-carboxyphenyl)porphyrin metal complex is selected, compared with tetrakis(4-carboxyphenyl)porphyrin, the porphyrin metal complex has the advantages of strong adsorption of lithium polysulfide and catalytic conversion of lithium polysulfide.
[0096] In one embodiment, the tetrakis(4-carboxyphenyl)porphyrin metal complex is a metal complex formed by tetrakis(4-carboxyphenyl)porphyrin and any one of iron ions, cobalt ions, nickel ions, and manganese ions; the tetrakis(4-carboxyphenyl)porphyrin metal complex is prepared by mixing tetrakis(4-carboxyphenyl)porphyrin with a metal salt and conducting a metalation reaction.
[0097] In order to better illustrate the present invention and provide an implementation method for reference, the preparation method of the tetrakis(4-carboxyphenyl)porphyrin metal complex is specifically to dissolve the tetrakis(4-carboxyphenyl)porphyrin in an organic solvent, add a metal salt, heat to 50-180°C and reflux for 1-12 hours, and then successively precipitate, filter, wash and dry to obtain the tetrakis(4-carboxyphenyl)porphyrin metal complex; wherein the metal salt is selected to include any one of ferric chloride, cobalt chloride, nickel chloride, and magnesium chloride, and the molar ratio of tetrakis(4-carboxyphenyl)porphyrin to the metal salt is 1:(1-1.5), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or any range or point value therebetween.
[0098] In one embodiment, the mass ratio of the tetrakis(4-carboxyphenyl)porphyrin / tetrakis(4-carboxyphenyl)porphyrin metal complex to the aqueous polyurethane resin is 1:(1-20), for example 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20 or any range or point value therebetween.
[0099] In the above technical scheme, the cross-linking agent is a cross-linking agent commonly used in the field of in-situ cross-linking reaction. The technicians in the field of this technology can select a suitable cross-linking agent according to actual needs. In one embodiment, for example, trimethylolpropane-tris[3-(2-methylaziridinyl)acrylate] is preferred, and the molar ratio of the aziridinyl group in the cross-linking agent to the carboxyl group in the waterborne polyurethane resin and the tetrakis(4-carboxyphenyl)porphyrin / tetrakis(4-carboxyphenyl)porphyrin metal complex is 1:(0.8-1.5), for example, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or any range or point value therebetween.
[0100] Herein, the stirring is a conventional stirring operation in the art, including magnetic stirring or mechanical stirring, and those skilled in the art can select a suitable stirring method according to the production scale or the current process conditions. In one embodiment, the stirring can be performed at a stirring rate of 100 to 800 rpm.
[0101] On the other hand, based on the aqueous binder for lithium-sulfur battery electrodes having electrocatalytic properties prepared as described above, in order to better illustrate the present invention and provide a reference application mode, the present invention also provides a method for preparing a sulfur electrode based on the aqueous binder for lithium-sulfur battery electrodes having electrocatalytic properties, comprising the following steps:
[0102] (1) Prepare the following raw materials by weight:
[0103] 50-90 parts of carbon-sulfur compound,
[0104] 3-20 parts of conductive carbon for electrodes,
[0105] 5 to 30 parts of aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties;
[0106] (2) The carbon-sulfur composite, the conductive carbon for the electrode, and the aqueous binder for the lithium-sulfur battery electrode having electrocatalytic performance prepared in step (1) are fully mixed and then coated on the surface of the electrode current collector by scraping, and dried to obtain a sulfur electrode.
[0107] In step (1), the carbon-sulfur composite is selected from conventional components in the sulfur electrode of a lithium-sulfur battery in the technical field. Those skilled in the art can know how to select and obtain the carbon-sulfur composite based on the records of lithium-sulfur batteries in the prior art.
[0108] In order to better illustrate the present invention and provide an implementation method for reference, the specific preparation method of the carbon-sulfur composite in step (1) is to mix the sublimated sulfur and carbon nanotubes in a weight ratio of 7:3 by ball milling, transfer the mixture to a reaction container, and heat the mixture at 155-160° C. for 15-20 hours under inert gas protection to obtain the carbon-sulfur composite.
[0109] In step (1), the conductive carbon for electrode is selected from conventional components in the sulfur electrode of lithium-sulfur batteries in the technical field. Those skilled in the art can know how to select and obtain conductive carbon for electrode based on the records of lithium-sulfur batteries in the prior art.
[0110] In order to better illustrate the present invention and provide an implementation method for reference, the conductive carbon for the electrode in step (1) is selected to include at least one of conductive carbon black, graphene, and carbon nanotubes.
[0111] In step (2), the fully mixing follows the principle of conventional chemical common sense, and the components are mixed evenly by means of mechanical stirring, etc. Under laboratory conditions, mechanical mixing for 10 to 30 minutes is usually sufficient to achieve a fully mixed effect. Considering the industrial scale-up effect, in the actual implementation of the conversion process, those skilled in the art may adopt a more appropriate fully mixing procedure according to the blending conditions of the components.
[0112] In this article, the scraping method in step (2) follows the common chemical common sense principle, and those skilled in the art can directly refer to the conventional dry electrode technology or the conventional film-forming method suitable for preparing sulfur electrodes reported in the literature.
[0113] In step (2), the electrode current collector is selected from conventional components in the sulfur electrode of a lithium-sulfur battery in the technical field. Those skilled in the art can know how to select and obtain the electrode current collector based on the records of lithium-sulfur batteries in the prior art.
[0114] It should be noted that if the coating does not have a suitable viscosity before the step (2), a small amount of solvent may be added.
[0115] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.
[0116] Example
[0117] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.
[0118] 1. Raw materials
[0119] Polyethylene glycol (PEG, Mw = ~4000), 2,2-dihydroxymethylpropionic acid (DMPA), N-methyldiethanolamine, isophorone diisocyanate (IPDI), triethylamine (TEA), ethylenediamine (EDA), hydrochloric acid (36.0% ~ 38.0%), N,N-dimethylformamide (DMF) (≥99.5%), carbon disulfide (CS2), isopropyl alcohol (IPA), and N-methylpyrrolidone (NMP) (≥99.0%) were purchased from Chengdu Kelong Chemical Reagent Co., Ltd.
[0120] Tetrakis(4-carboxyphenyl)porphyrin (>98%), ferric chloride, cobalt chloride, manganese chloride, nickel chloride, and deuterated chloroform (99.8%) were purchased from Shanghai Titan Technology Co., Ltd. Aziridine crosslinker HD-100A was purchased from Ningxia Zhuoyu New Materials Technology Co., Ltd. Multi-walled carbon nanotubes (MWCNT) (>98%) were purchased from Shenzhen Suiheng Technology Co., Ltd. Single-layer graphene (battery grade) was purchased from Suzhou Tanfeng Graphene Technology Co., Ltd. Conductive carbon black Super P (battery grade) was purchased from Swiss Temeco.
[0121] Polyvinylidene fluoride (PVDF) (battery grade) was purchased from Shanghai Lanbai Technology Co., Ltd. LS-001 electrolyte (battery grade) was purchased from Suzhou Duoduo Chemical Technology Co., Ltd. Lithium sulfide (≥99.9%) was purchased from MacLean Biochemical Technology Co., Ltd. Polypropylene diaphragm (battery grade) was purchased from Jiangxi Enbo New Materials Co., Ltd. Deionized water was used in all experiments. Unless otherwise specified, all reagents were of analytical reagent (AR) grade quality and were used without further purification.
[0122] 2. Test Method
[0123] 180° peel test: When preparing the sample, the back of the positive electrode sheet (24 mm wide and 50 mm long) prepared with different adhesives was first attached to the glass slide with double-sided tape, and then the front was fixed on the tape. The double-column table test machine (INS Tron Universal Material Testing Machine 5967, USA) was used at a constant tensile speed of 10 mm / min. -1 Record the applied load on the sample.
[0124] Constant current charge and discharge test: In the present invention, the MIHW-200-160CH constant temperature test chamber of Shenzhen Xinwei Company is used to perform constant current charge and discharge tests on the battery at different cycle periods and different charge and discharge rates. The nominal specific capacity is 1675mAh g -1 The test voltage was 1.7V to 2.8V, the temperature was 30°C, and the scan rate was 0.033mV s -1 Lithium-sulfur batteries based on different binders were assembled and tested to explore the effect of the prepared binder on the electrochemical performance of the sulfur cathode.
[0125] Constant current intermittent titration technology: Constant current intermittent titration (GITT) is a test technology for reaction kinetics obtained by analyzing the relationship between potential and time. A complete GITT test consists of multiple sets of "current step" units. In each current step unit, the battery is charged (discharged) at a constant current for a period of time at a small current, and then the current is cut off and maintained for a period of time to allow the ions to fully diffuse in the active material to reach a balanced state. By analyzing the relationship between the change in electrode potential and the relaxation time, the diffusion coefficient of the ions inside is calculated.
[0126] Electrochemical impedance spectroscopy: The electrochemical impedance spectroscopy (EIS) test of lithium-sulfur batteries was performed using Shanghai Chenhua Instrument Co., Ltd. CHI 600E electrochemical analyzer / workstation to characterize electrode performance and electron transfer resistance, etc. The test frequency range was 100 Hz to 0.01 Hz, and the amplitude was 10 mV.
[0127] Cyclic voltammetry test: In the present invention, a CHI 600E electrochemical analyzer / workstation from Shanghai Chenhua Instrument Co., Ltd. was used to perform cyclic voltammetry (CV) on the lithium-sulfur battery to characterize the redox reaction occurring at the electrode and explore its mechanism. The scan rate was 0.1 mV s -1 .
[0128] Scanning electron microscope test: Scanning electron microscope (SEM) uses a focused high-energy electron beam to scan the sample surface and analyzes the surface structure of the material by collecting the excited secondary electrons. In the present invention, after the sample was treated with gold spraying, it was studied using a JEOL JEM-F200 field emission transmission electron microscope at an acceleration voltage of 5 kV.
[0129] Example 1
[0130] This embodiment prepares a high molecular weight waterborne polyurethane resin having carboxyl groups in its molecular chain, and the specific preparation steps are as follows:
[0131] Polyethylene glycol, 2,2-dimethylol propionic acid, N-methyldiethanolamine and isophorone diisocyanate are used as raw materials, mixed evenly, and reacted at 90°C for 5 hours to prepare an isocyanate-terminated prepolymer; then the prepolymer is cooled to 30°C, triethylamine is added to neutralize the carboxyl group to form a salt, and then added to deionized water for uniform dispersion and emulsification, and ethylenediamine is used as a chain extender, ethylenediamine is added dropwise at 30°C and stirred for reaction for 1 hour to prepare a high molecular waterborne polyurethane resin with carboxyl groups in the molecular chain;
[0132] The molar ratio of the polyethylene glycol, 2,2-dimethylolpropionic acid, N-methyldiethanolamine, isophorone diisocyanate triethylamine, and ethylenediamine is 1:1:1:6:1:3;
[0133] The amount of deionized water added is 3 times the mass of the prepolymer after salt treatment.
[0134] Example 2
[0135] This example uses the high molecular weight waterborne polyurethane resin having carboxyl groups in the molecular chain prepared in Example 1, and in-situ crosslinks it with metal porphyrin to prepare a waterborne binder for lithium-sulfur battery electrodes having electrocatalytic properties, which mainly includes the following steps:
[0136] Tetrakis(4-carboxyphenyl)porphyrin is dissolved in DMF, ferric chloride is added, the temperature is raised to 150°C and refluxed for 6 hours, and then the tetrakis(4-carboxyphenyl)porphyrin metal complex is prepared by precipitation, filtration, washing and drying in sequence; the molar ratio of tetrakis(4-carboxyphenyl)porphyrin to ferric chloride is 1:1;
[0137] Tetrakis(4-carboxyphenyl)porphyrin metal complex and waterborne polyurethane resin are added into a reaction container in a mass ratio of 1:1, trimethylolpropane-tris[3-(2-methylaziridinyl)acrylate] is added, and after being fully stirred, a waterborne binder for lithium-sulfur battery electrodes with electrocatalytic performance is obtained, which is recorded as Fe-PWPU;
[0138] The molar ratio of the propidium group in the trimethylolpropane-tris[3-(2-methylaziridinyl)acrylate] to the carboxyl group in the waterborne polyurethane resin and the tetrakis(4-carboxylphenyl)porphyrin metal complex is 1:1.
[0139] Example 3
[0140] Example 3 follows the steps of Example 2, except that the ferric chloride is replaced with manganese chloride to prepare a lithium-sulfur battery electrode aqueous binder with electrocatalytic properties, which is recorded as Mn-PWPU.
[0141] Example 4
[0142] Example 4 follows the steps of Example 2, except that the ferric chloride is replaced with cobalt chloride to prepare a lithium-sulfur battery electrode aqueous binder with electrocatalytic properties, which is recorded as Co-PWPU.
[0143] Example 5
[0144] Example 5 follows the steps of Example 2, except that the ferric chloride is replaced by nickel chloride to prepare a lithium-sulfur battery electrode aqueous binder with electrocatalytic properties, which is denoted as Ni-PWPU.
[0145] Example 6
[0146] This example uses the aqueous binder for lithium-sulfur battery electrodes with electrocatalytic performance prepared in Example 2 to prepare a sulfur electrode for testing, comprising the following steps:
[0147] (1) Prepare the following raw materials by weight:
[0148]
[0149]
[0150] The specific preparation method of the carbon-sulfur composite is to mix sublimated sulfur and carbon nanotubes in a weight ratio of 7:3 by ball milling, transfer the mixture to a reaction container, and heat at 155° C. for 15 hours under inert gas protection to prepare the carbon-sulfur composite.
[0151] (2) The carbon-sulfur composite, conductive carbon black, graphene and aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties prepared in step (1) are mixed thoroughly and then coated on the surface of aluminum foil with a scraper. The active material loading is 1 mg / cm 2 After vacuum drying at room temperature and 50 °C, the prepared sulfur electrode was used as a sample, denoted as S@Fe-PWPU.
[0152] Example 7
[0153] Example 7 follows the steps of Example 6 and uses the aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties prepared in Example 3 to prepare a sulfur electrode for testing as a sample, which is recorded as S@Mn-PWPU.
[0154] Example 8
[0155] Example 8 follows the steps of Example 6 and uses the aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties prepared in Example 4 to prepare a sulfur electrode for testing as a sample, which is recorded as S@Co-PWPU.
[0156] Example 9
[0157] Example 9 follows the steps of Example 6 and uses the aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties prepared in Example 5 to prepare a sulfur electrode for testing as a sample, which is recorded as S@Ni-PWPU.
[0158] Example 10
[0159] This example uses the high molecular weight waterborne polyurethane resin having carboxyl groups in the molecular chain prepared in Example 1, and in-situ crosslinks it with porphyrin to prepare a waterborne binder for lithium-sulfur battery electrodes having electrocatalytic properties, which mainly includes the following steps:
[0160] Tetrakis(4-carboxyphenyl)porphyrin and waterborne polyurethane resin are added into a reaction container in a mass ratio of 1:1, trimethylolpropane-tris[3-(2-methylaziridinyl)acrylate] is added, and after being fully stirred, a waterborne binder for lithium-sulfur battery electrodes having electrocatalytic performance is obtained, which is recorded as PWPU;
[0161] The molar ratio of the propidium group in the trimethylolpropane-tris[3-(2-methylaziridinyl)acrylate] to the carboxyl group in the waterborne polyurethane resin and tetrakis(4-carboxyphenyl)porphyrin is 1:1.
[0162] Comparative Example 1
[0163] Comparative Example 1 is to prepare a comparative sulfur electrode for testing using a conventional commercial battery binder (PVDF), comprising the following steps:
[0164] (1) Prepare the following raw materials by weight:
[0165]
[0166] The specific preparation method of the carbon-sulfur composite is to mix sublimated sulfur and carbon nanotubes in a weight ratio of 7:3 by ball milling, transfer the mixture to a reaction container, and heat at 155° C. for 15 hours under inert gas protection to prepare the carbon-sulfur composite.
[0167] (2) The carbon-sulfur composite, conductive carbon black, graphene and PVDF prepared in step (1) were fully mixed and then coated on the surface of aluminum foil. After vacuum drying at room temperature and 50° C., a sulfur electrode was prepared as a comparative sample, denoted as S@PVDF.
[0168] In order to test the sulfur electrodes prepared in Examples 6 to 9 and Comparative Example 1, the obtained sulfur electrodes were used as positive electrodes to assemble lithium-sulfur batteries. The battery shell included a positive electrode shell and a negative electrode shell, both of which were made of 316 stainless steel, and a polypropylene diaphragm was used as the diaphragm. The spring and the gasket were placed in the negative electrode shell in sequence, and then the metal lithium negative electrode and the diaphragm were placed on the gasket in sequence, and then the commercial electrolyte was injected into the diaphragm, and then the positive electrode was placed, and the positive electrode shell was used for sealing. Specifically, a pressure-controlled electric button battery packaging machine was used to package the button half-cell.
[0169] 3. Test results
[0170] Figure 1 This is a schematic diagram of the chemical structure of the aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties prepared in Example 3 of the present invention.
[0171] Figure 2 The test results of the 180° peel test of the sulfur electrode samples prepared in Example 7 and Comparative Example 1 of the present invention are shown in Figure 1. According to the image, the average peel force of S@Mn-PWPU is 4.78N, which is much higher than the peel force of S@PVDF (1.58N). By characterizing the morphology of the electrode after the peeling process ( Figure 2 (b)), it can be seen that Mn-PWPU can keep most of the active materials on the current collector, and only a small part of the active materials fall off, which is mainly due to the three-dimensional structure of Mn-PWPU after in-situ cross-linking. The weak bonding performance of PVDF causes most of the active materials to fall off.
[0172] Figure 3After the sulfur electrode samples prepared in Example 7 and Comparative Example 1 of the present invention were immersed in 1 mL of LS-001 electrolyte for 12 hours, their swelling ratio was calculated based on the weight difference of the sulfur positive electrode before and after immersion. The swelling ratio of S@Mn-PWPU reached 195%, which was significantly higher than that of S@PVDF (123%), indicating that the electrode sheet prepared using the aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties has good electrolyte affinity. Figure 3 (b) It can be seen that S@Mn-PWPU did not peel off or fall off, and had good solvent resistance, stability and adhesion; while S@PVDF had electrode shedding, indicating that it could not bond the active material and the current collector well.
[0173] Figure 4 The 1C cycle performance test of the battery assembled with the sulfur electrode samples prepared in Examples 6 to 9 of the present invention and Comparative Example 1. The first cycle specific capacities of S@PVDF, S@Fe-PWPU, S@Co-PWPU, S@Ni-PWPU and S@Mn-PWPU at 1C are 1293 mAh g -1 , 1365mAh g -1 , 1396mAh g -1 , 1407mAh g -1 , 1344mAh g -1 The capacity after 200 cycles of stable constant current charge and discharge at 1C is 640mAh g -1 , 687mAh g -1 , 707mAh g -1 , 717mAh g -1 , 724mAh g -1 , the capacity retention rates were 49.50%, 50.33%, 50.64%, 50.96% and 53.87% respectively. The average capacity loss per cycle was 0.35%, 0.34%, 0.34%, 0.34% and 0.31% respectively, and the coulombic efficiency after 200 cycles was 97.35%, 96.52%, 97.67%, 97.59% and 97.58% respectively. The cycle attenuation rate of S@PVDF is higher, and due to its low initial capacity, it is not much higher than the sulfur electrode prepared by other binders in the experiment. The above results show that the aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties provided by the present invention has excellent performance in sulfur positive electrodes, and has high initial capacity and capacity retention rate. However, the active material loss on the electrode based on PVDF binder is relatively large, and a large amount of lithium polysulfide has a "shuttle effect". In addition, it is difficult for the binder to maintain the stability of the electrode structure, resulting in a significant decrease in specific capacity, resulting in a decrease in electrode cycle performance and even battery failure.
[0174] Figure 5The rate performance test results of the battery assembled from the sulfur electrode samples prepared in Examples 6 to 9 of the present invention and Comparative Example 1. The aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties has better rate performance than PVDF at different rates. At 0.2C and 5C, the discharge specific capacity of S@Mn-PWPU reached 1147.93 mAh g -1 and 274.82mAhg -1 Meanwhile, S@PVDF is only 1129.32 mAh g -1 and 27.91mAh g -1 , indicating that the binder of the present invention can effectively improve the lithium polysulfide conversion capacity of the battery under high rate conditions. After the current density is restored to 0.2C, the positive electrode prepared by the binder provided in Example 3 still has 951.56 mAh g -1 Due to the huge capacity difference during 5C discharge, the discharge time is significantly different. Therefore, when the rate returns to 0.2C, S@PVDF still has 997.61mAh g -1 The above results show that the sulfur electrodes provided by Examples 6 to 9 have excellent fast charge and discharge capabilities and high power output capabilities, while the capabilities of S@PVDF in high power and fast charge and discharge scenarios are relatively poor.
[0175] Figure 6 The GITT curves of the battery assembled with the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1 are shown. Compared with S@PVDF, S@Mn-PWPU has a smaller polarization voltage (charge and discharge platform voltage difference) and a longer discharge platform, indicating that Mn-PWPU contributes to the redox kinetics of Li-S batteries. The internal resistance during nucleation and activation is shown in Figure 1, ΔR internal It can be calculated by the following formula:
[0176] ΔR internal (Ω)=|ΔV QOCV-CCV | / I applied .
[0177] Figure 7 The EIS curves of the battery assembled with the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1. The EIS test shows a semicircular area in the high frequency range, which represents the transfer resistance (R ct ). The transfer resistance (R ct ) is 12.87Ω, which is lower than the R ct(32.61Ω). This indicates that compared with PVDF, the designed binder has higher ionic conductivity. The Mn-PWPU binder contains a large number of ion-conducting PEG segments, which can better bond the active material with the conductive agent and fix it on the current collector, thereby improving the transmission of electrons and lithium ions, making the battery resistance lower and having better cycle performance.
[0178] Figure 8 Cyclic voltammetry curves of batteries assembled from the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1. Figure 8 Reflecting the kinetics of the redox reaction, peaks i and ii are the reduction of sulfur to higher-order lithium polysulfides LiPSs (Li2S n , 4≤n≤8) and the process in which high-order LiPSs are reduced to low-order LiPSs (Li2S2 and Li2S). Compared with S@PVDF, the interval between the oxidation peak and the reduction peak of S@Mn-PWPU is smaller and the intensity is higher, showing smaller voltage polarization and more favorable reaction kinetics.
[0179] exist Figure 8 The conclusion that "the smaller the interval between the oxidation peak and the reduction peak, the higher the intensity, the smaller the voltage polarization and the more favorable the reaction kinetics" can be found in the following literature:
[0180] 1.Senthil C,Kim SS,Jung H Y.Flame retardant high-power Li-S flexiblebatteries enabled by bio-macromolecular binder integrating conformalfractions[J].Nature Communications,2022,13(1):145.
[0181] Fig. 9 The images of the battery assembled with the sulfur electrode samples prepared in Example 7 of the present invention and Comparative Example 1 after 200 cycles at 1C show that there is no shedding of S@Mn-PWPU and no obvious lithium polysulfide residue on the diaphragm; while the corresponding S@PVDF positive electrode has obvious shedding, and dark yellow lithium polysulfide also appears on the diaphragm. This shows that the stability of the sulfur positive electrode prepared based on Mn-PWPU binder is significantly better than that of the sulfur positive electrode prepared based on PVDF.
[0182] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high molecular weight waterborne polyurethane resin having carboxyl groups in its molecular chain, characterized in that The chemical structure is as follows: Wherein, n=1-100, R1 is the following structure: R2 is any of the following structures: R3 is any one of the following structures, m=10-200:
2. A method for preparing a high molecular weight waterborne polyurethane resin having carboxyl groups in its molecular chain, characterized in that The following steps are involved: Polymeric diol, 2,2-dihydroxymethylpropionic acid, N-methyldiethanolamine and diisocyanate are selected as raw materials, mixed evenly and reacted at a temperature of 30-100° C. for 0.5-12 hours to prepare an isocyanate-terminated prepolymer; the prepolymer is then cooled to 0-80° C., neutralized with a carboxyl group and subjected to a salt treatment, and then emulsified and chain extended using a water-soluble diamine as a chain extender to prepare a high molecular weight waterborne polyurethane resin having a carboxyl group in the molecular chain.
3. The preparation method according to claim 2, characterized in that: The polymeric diol includes any one of polyethylene glycol, polypropylene glycol and polytetramethylene glycol, and the molecular weight of the polymeric diol ranges from 600 to 10,000.
4. The preparation method according to claim 2, characterized in that: The diisocyanate includes any one of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, toluene diisocyanate and hexamethylene diisocyanate.
5. The preparation method according to claim 2, characterized in that: The molar ratio of the polymeric diol, 2,2-dimethylol propionic acid, N-methyldiethanolamine and diisocyanate is 1:(1-1.5):(1-1.5):(4-8).
6. A water-based binder for lithium-sulfur battery electrodes having electrocatalytic properties prepared by in-situ crosslinking of the water-based polyurethane resin of claim 1 with porphyrin / metalloporphyrin, characterized in that The main steps include: Tetrakis(4-carboxyphenyl)porphyrin / tetrakis(4-carboxyphenyl)porphyrin metal complex and waterborne polyurethane resin are added into a reaction container in a mass ratio of 1:(1-20), a crosslinking agent is added, and the mixture is fully stirred to obtain a waterborne binder for lithium-sulfur battery electrodes with electrocatalytic properties.
7. The aqueous binder for lithium-sulfur battery electrodes according to claim 6, characterized in that: The tetrakis(4-carboxyphenyl)porphyrin metal complex is a metal complex formed by tetrakis(4-carboxyphenyl)porphyrin and any one of iron ions, cobalt ions, nickel ions and manganese ions; the tetrakis(4-carboxyphenyl)porphyrin metal complex is prepared by mixing tetrakis(4-carboxyphenyl)porphyrin with a metal salt and performing a metallization reaction.
8. Use of the aqueous binder for lithium-sulfur battery electrodes having electrocatalytic properties as claimed in claim 6 in the preparation of lithium-sulfur batteries.
9. A method for preparing a sulfur electrode based on the aqueous binder for lithium-sulfur battery electrodes having electrocatalytic properties as claimed in claim 6, characterized in that The following steps are involved: (1) Prepare the following raw materials by weight: 50-90 parts of carbon-sulfur compound, 3-20 parts of conductive carbon for electrodes, 5 to 30 parts of aqueous binder for lithium-sulfur battery electrodes with electrocatalytic properties; (2) The carbon-sulfur composite, the conductive carbon for the electrode, and the aqueous binder for the lithium-sulfur battery electrode having electrocatalytic performance prepared in step (1) are fully mixed and then coated on the surface of the electrode current collector by scraping, and dried to obtain a sulfur electrode.
10. The sulfur electrode prepared by the sulfur electrode preparation method according to claim 9.
Citation Information
Patent Citations
Preparation method of amphoteric ion type polyurethane hydrogel
CN105906781A
Preparation method of anionic-cationic waterborne polyurethane and prepared waterborne polyurethane
CN114573782A
Amphoteric polyurethane having side chain with acid and base groups and its preparation method
CN1260356A
Binder for electrode of lithium secondary battery, and lithium secondary battery using electrode manufactured using the binder
JP2014191942A
Polyurethane resin water dispersion
JP2016188362A
Cited By
Solid-state lithium-sulfur battery, manufacturing method thereof and electric equipment
CN120221782A
Molecular bridging binder for solid-state lithium-sulfur batteries and method of making same
CN122686273A